The Influence of Ownership Structure, Financial Condition and Company Size on Company Financial Performance - Kinanti Arka Ramadhaniar; Mahameru Rosy Rochmatullah (Community Engagement and Emergence Journal (CEEJ), 2025)
In today's globalized world, business rivalry is fiercer than ever, necessitating a competitive advantage for organizations to thrive and remain market leaders. This study's goal is to analyze how ownership structure, firm size, and financial standing affect financial performance. Until the end of 2023, ciblé procedures were used to choose the sample from the population of manufacturing companies. Tests of hypotheses, multiple linear regression tests, verifications of classical hypotheses, and descriptive statistical tests were all part of the analysis approach. The results of the tests and the data analysis demonstrate that management ownership influences financial success. Institutional ownership (KI) influences financial performance. Leverage (DER) influences financial performance. Liquidity (CR) influences financial performance. Financial performance is determined by company size (UKPER). Financial success is determined by Total Asset Turnover (TATO).